Electromyographic and Clinical Investigation of the Effect of Platelet-Rich Plasma on Peripheral Nerve Regeneration in Patients with Diabetes after Surgery for Carpal Tunnel Syndrome - Yasak, Tuğçe; Özkaya, Özay; Ergan Şahin, Ayça; Çolak, Özlem (Archives of Plastic Surgery, 2022)
Background Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy. Studies have shown that results of CTS surgery are poorer in patients with diabetes. In this study, the effect of platelet-rich plasma (PRP) on nerve regeneration was investigated through clinical and electromyographic findings in patients with diabetes who underwent CTS surgery.Methods A retrospective analysis of 20 patients with diabetes who had surgically decompressed CTS was conducted. Patients were divided into two groups. The study group received PRP treatment following surgery. The control group did not receive any treatment. Patients were assessed using electromyography and the Boston Carpal Tunnel Syndrome Questionnaire preoperatively as well as postoperatively at 3-month, 6-month, and 1-year follow-ups visits.Results There was a decrease in complaints and an improvement in sensory and motor examinations in both groups. The Boston Carpal Tunnel Syndrome Questionnaire scores did not show any statistically significant differences between the two groups. However, electromyographic findings showed that there were statistical differences between preoperative and postoperative (3 months, 6 months, and 1 year) results in both groups. When the two groups were compared using preoperative and postoperative (3 months, 6 months, and 1 year) electromyographic values, no statistically significant differences were seen.Conclusion Single injections of PRP did not have a significant impact on median nerve regeneration following CTS surgery in patients with diabetes. The effectiveness of multiple PRP injections can be investigated in patients with diabetes in future studies.
Keywords: diabetes mellitus; carpal tunnel syndrome; median nerve; nerve regeneration; platelet-rich plasma